2018
DOI: 10.1111/acel.12815
|View full text |Cite
|
Sign up to set email alerts
|

In vivo GDF3 administration abrogates aging related muscle regeneration delay following acute sterile injury

Abstract: Tissue regeneration is a highly coordinated process with sequential events including immune cell infiltration, clearance of damaged tissues, and immune‐supported regrowth of the tissue. Aging has a well‐documented negative impact on this process globally; however, whether changes in immune cells per se are contributing to the decline in the body’s ability to regenerate tissues with aging is not clearly understood. Here, we set out to characterize the dynamics of macrophage infiltration and their functional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
8
25
0
Order By: Relevance
“…Consistent with recent studies, we found that when compared to young mice, aged muscle showed an increased basal presence of both PMNs (Sloboda et al, 2018) and resident M2-like MΦ (Cui et al, 2019;Reidy et al, 2019;Sorensen et al, 2019;Wang et al, 2015). Aged mice also mounted a heightened acute inflammatory response to myofiber injury induced by intramuscular injection of BaCl2 which is consistent with prior studies of muscle damage induced by lengthening contractions (Koh, Peterson, Pizza, & Brooks, 2003;Sloboda et al, 2018), myotoxin injection (Patsalos et al, 2018;van der Poel et al, 2011), or contusion (Ghaly & Marsh, 2010). LC-MS/MS based profiling of the mediator lipidome revealed that both chronic low-grade muscle inflammation and excessive acute myeloid cell responses in muscle injury were associated with a marked deficiency in local concentrations of SPMs and their key pathway markers, suggesting that pro-resolving therapies may benefit agerelated muscle dysfunction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with recent studies, we found that when compared to young mice, aged muscle showed an increased basal presence of both PMNs (Sloboda et al, 2018) and resident M2-like MΦ (Cui et al, 2019;Reidy et al, 2019;Sorensen et al, 2019;Wang et al, 2015). Aged mice also mounted a heightened acute inflammatory response to myofiber injury induced by intramuscular injection of BaCl2 which is consistent with prior studies of muscle damage induced by lengthening contractions (Koh, Peterson, Pizza, & Brooks, 2003;Sloboda et al, 2018), myotoxin injection (Patsalos et al, 2018;van der Poel et al, 2011), or contusion (Ghaly & Marsh, 2010). LC-MS/MS based profiling of the mediator lipidome revealed that both chronic low-grade muscle inflammation and excessive acute myeloid cell responses in muscle injury were associated with a marked deficiency in local concentrations of SPMs and their key pathway markers, suggesting that pro-resolving therapies may benefit agerelated muscle dysfunction.…”
Section: Discussionsupporting
confidence: 87%
“…These data suggest that RvD1 was unable to fully overcome heightened muscle myeloid cell infiltration in aged mice. This may relate to the fact that as in prior studies expression of many inflammation-related genes was increased in aged muscle even before injury (Cui et al, 2019;Lavin et al, 2020;Patsalos et al, 2018;Rivas et al, 2016;van der Poel et al, 2011;Wang et al, 2015;Wang et al, 2018). Furthermore, the degeneracy of SPMs may also suggest that a single immunoresolvent class (RvD1 used here) may be insufficient for the overall resolution of inflammation following muscle injury, especially in aged mice that were deficient in a range of different SPM families.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…ii) A dysfunctional inflammatory response. As detailed in this study, local inflammation is high at rest and slow to activate in response to injury in old mice, a phenomenon observed by others 25 . Therefore improving muscle repair processes in old mice will require tackling both satellite cell and immune cell deficiencies.…”
Section: Discussionsupporting
confidence: 77%
“…For example, Varga et al reported that GDF3 could serve as an exclusively macrophage-derived factor in the restoration of skeletal muscle integrity [10]. Patsalos et al further observed that tissue-repairing macrophages could secret GDF3, which was markedly downregulated in the injured muscle of old mice relative to young mice [11]. Furthermore, GDF3 has been demonstrated to be an essential mediator for adipose tissue macrophage (ATM)-mediated fat metabolism [12].…”
Section: Introductionmentioning
confidence: 99%